Exploration of Plant Disturbing Organisms (PDOs) in Trembesi (Samanea saman) Seedlings in Tectona Bukit Soeharto Seedlings - Rucmana Saud, Oshlifin; Syarifudin, Achmad; Rafii Nur Fauzan, Muhammad Rafii; Nugroho, Andi; Sri Utami, Widia (CELEBES Agricultural, 2025)
The seedling phase is a critical stage in plant development, where the presence of plant-disturbing organisms (PDOs) can significantly reduce seedling quality and viability, particularly in rehabilitation species such as Samanea saman (Trembesi). This study aimed to analyze the intensity of pest and disease attacks, identify the types of PDOs involved, and describe the symptoms and signs of infestation observed in S. saman seedlings at the Tectona Nursery, KHDTK Bukit Soeharto, East Kalimantan. A simple random sampling method was applied to select 50 seedlings from a total population of 1,000 four-month-old individuals. Data collection was conducted through direct field observation of physical plant conditions, severity scoring, and documentation of symptoms and signs of biotic attack. The results showed that all sampled seedlings were affected, with an infestation intensity reaching 65.2%, classified as heavily infested. The observed symptoms included defoliation, foliar tissue loss (skeletonizing), leaf spots, leaf blight, and stem boring. Identified signs of attack included larvae from the order Lepidoptera and  mealybug (Pseudococcidae) and aphids, which are suspected to be the primary agents of tissue damage. These findings underscore the importance of monitoring pest and disease populations and implementing ecologically based Integrated Pest Management (IPM) strategies tailored to the nursery microclimate. Technical training and coordinated IPM implementation are essential to enhance seedling resilience and support the success of tropical forest rehabilitation.